Intellectual capital, organisational climate, innovation culture, and SME performance: Evidence from Croatia. Issue 4 (8th October 2018) - Dabić, Marina; Lažnjak, Jasminka; Smallbone, David; Švarc, Jadranka
Abstract : Purpose: The purpose of this paper is to analyse the relationship between the three components of intellectual capital (IC) (human, structural, and relational), and contextual factors relating to organisational climate (OC) and innovation culture, together with their influence on business performance (BP). Design/methodology/approach: This empirical research is based on an online questionnaire, which collected data from a non-probability quota sample consisting of 253 Croatian SMEs. The scales for IC, OC, and innovation culture were constructed to test the relationship between these dimensions and assess the BP of the SMEs. Findings: Based on a survey on 253 SMEs in Croatia, the analysis shows that the key dimensions of IC, innovation culture, and OC are vital to a company's success and are strongly inter-correlated. Higher BP is positively related to higher levels of both IC and innovation culture. Research limitations/implications: The main limitation of the research is the subjective aspect of the study. The data used in the study were self-reported where respondents in a survey gave their assessment of firm performance. Although this was necessary because of the absence of other data, it is an issue that must be taken into account when interpreting the findings in the study. Practical implications: Understanding the role of IC, OC, and innovation culture in relation to BP, particularly in former transition countries, can have important implications for managers and enterprise owners, as well as policy makers and the academic community. Social implications: The findings emphasise the important role of tacit knowledge in the innovation process, of which IC and OC are good examples. Originality/value: This empirical study brings evidence from the understudied country of Croatia. Croatia is a post-transitional country and the last accessed member of the EU, on the dividing line between a modest and a moderate innovator. This is the first empirical study conducted in Croatia that explores the association between three concepts that are typically investigated separately (IC, OC, and innovation culture).